A case of left atrial haemangioma: echocardiographic, surgical, and morphological features. Issue 6 (December 1987) - Weir, I; Mills, P; Lewis, T
Abstract : A slow growing encapsulated haemangioma of the left atrium was diagnosed by means of cross sectional echocardiography. The heterogeneous nature of the tumour was reflected in a central area of relative echolucency. After successful surgical removal of the tumour, the patient's symptoms of lethargy and limited exercise capacity improved considerably.